Transportation of Fe3O4-SiO2-Al2O3/EO and SiO2-Al2O3/EO nanoparticles in magnetized Reiner–Philippoff liquid, including modified fluxes via Galerkin algorithm: Significance of EMHD - Sohail, Muhammad; Nazir, Umar; Mukdasai, Kanit; Singh, Manoj; Singh, Abha; Mohan, Chandika Rama; Galal, Ahmed M.; Eldin, Sayed M. (Frontiers in Physics, 2023)
This developing study is focused on mass diffusion and thermal energy enhancement in Reiner–Philippoff martial across a vertical-surface under an exposed Lorentz force. Characterization of the thermal energy and mass diffusion are modified utilizing non-Fourier’s theory in the presence of a heat source. Three types of nanoparticles—Al2O3, titanium dioxide, and TiO2—in engine oil are inserted for production of heat energy. Darcy’s Forchheimer theory is used to analyze behavior flow and heat energy. Moreover, effects related to Dufour and Soret are added. A transformed system of ODEs is achieved regarding the developed model using similarity variables. Numerically developing models in the form of ODEs are handled with the aid of the finite element method (FEM). Fluidic thermal energy is augmented against upshot values of time relaxation number. Fluidic concentration declines against changes in Schmidt number and chemical reaction number.